Ultrafine Particle Distribution and Chemical Composition Assessment during Military Operative Trainings - Campagna, Marcello (Int J Environ Res Public Health, 2017)
(1) Background: The assessment of airborne particulate matter (PM) and ultrafine particles (UFPs) in battlefield scenarios is a topic of particular concern; (2) Methods: Size distribution, concentration, and chemical composition of UFPs during operative military training activities (target drone launches, ammunition blasting, and inert bomb impact) were investigated using an electric low-pressure impactor (ELPI+) and a scanning electron microscope (SEM), equipped with energy-dispersive spectroscopy (EDS); (3) Results: The median of UFPs, measured for all sampling periods and at variable distance from sources, was between 1.02 × 10(3) and 3.75 × 10(3) particles/cm(3) for drone launches, between 3.32 × 10(3) and 15.4 × 10(3) particles/cm(3) for the ammunition blasting and from 7.9 × 10(3) to 1.3 × 10(4) particles/cm(3) for inert launches. Maximum peak concentrations, during emitting sources starting, were 75.5 × 10(6) and 17.9 × 10(6) particles/cm(3), respectively. Particles from the drone launches were predominantly composed of silicon (Si), iron (Fe) and calcium (Ca), and those from the blasting campaigns by magnesium (Mg), sulphur (S), aluminum (Al), iron (Fe), barium (Ba) and silicon (Si); (4) Conclusions: The investigated sources produced UFPs with median values lower than other anthropogenic sources, and with a similar chemical composition.